2022
DOI: 10.3389/fpubh.2021.752204
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Patterns of Food Procurement Over the Course of the COVID-19 Pandemic: Findings From a Canadian Online Household Survey

Abstract: IntroductionConsumer food procurement during the COVID-19 pandemic has been understudied. This investigation aimed to longitudinally evaluate food procurement patterns, concern of virus exposure in grocery retailers, and food access challenges over the pandemic among a sample of households in Quebec, Canada.MethodsOnline surveys were collected at three time points of the pandemic: first wave in spring 2020 (lockdown period), summer 2020 (deconfinement period), and second wave in winter 2021 (curfew period). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Furthermore, personal consumption of supplements and non-prescription drugs, which are available via online shopping, also increased, whereas expenditures for medical expenses that require visits to medical facilities decreased ( 63 , 64 ). These results suggest that individuals reduced visits to buy daily necessaries and purchased more on each visit for reducing the risks of COVID-19 exposure ( 41 , 42 , 44 ). Individuals also turned to online shopping, resulting in considerable changes to retail and commerce ( 41 , 44 , 65 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, personal consumption of supplements and non-prescription drugs, which are available via online shopping, also increased, whereas expenditures for medical expenses that require visits to medical facilities decreased ( 63 , 64 ). These results suggest that individuals reduced visits to buy daily necessaries and purchased more on each visit for reducing the risks of COVID-19 exposure ( 41 , 42 , 44 ). Individuals also turned to online shopping, resulting in considerable changes to retail and commerce ( 41 , 44 , 65 ).…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have revealed that individuals experienced changes in their daily lifestyles during the pandemic; for instance, an increase in online activities replaced physical participation and contributed to changes in urban mobility ( 39 42 ). During the restriction on restaurants/pubs (April-June 2020), the night-time population in Tokyo decreased ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the time data were collected (between May-June 2020), grocery store visits across Canada were largely limited to one visit or less per week, and while food access was not reported to be problematic amongst the general population, there was a notable lack of availability of canned or frozen fruits and vegetables, and grain products (19). One possible explanation for the increased direct grocery costs among lower income food-allergic families with food procurement difficulties is that these families are obliged to buy more expensive alternatives when faced with product shortages.…”
Section: Discussionmentioning
confidence: 99%
“…Confinement inevitably disturbs lifestyle behaviors, such as eating habits, physical activity level, and sleep, to varying degrees among individuals [3]. Although some observational studies and surveys have reported more home cooking, better diet quality, and increased physical activity levels [4,5], others have observed decreased physical activity, increased energy and alcohol intake, binge eating, reliance on take-out foods, and overall decreased diet quality [6][7][8]. The combination of poor diet quality, low physical activity, and greater alcohol intake, BMI, and smoking represents an important risk for severe COVID-19 [9], COVID-19 mortality [10], and chronic diseases during the postpandemic period [11].…”
Section: Introductionmentioning
confidence: 99%